PENGEMBANGAN INSTRUMEN LITERASI NUMERASI KONTEKS SOSIAL BUDAYA DI SMK PLUS PAKUHAJI - Muhamad Yasin; Hepsi Nindiasari; Sukirwan Sukirwan (LPPM Universitas Bina Bangsa, 2023)
This study aims to produce a Vocational Mathematics numeracy literacy instrument that has been tested for validity and reliability, as well as through a systematic analysis of the instrument using a test of discrimination and index of difficulty. This type of research is development research with the Wilson model and the Oriondo and Antonio models. Methods of data collection using interviews, expert validation sheets, questionnaires and numeracy literacy tests. Data were analyzed descriptively and quantitatively. The research results obtained were: 1) the expert's assessment stated that this numeracy literacy instrument was an appropriate instrument to use; 2) the readability test shows that this numeracy literacy instrument is in the